PROBLEMATIK PASAL PENGHINAAN TERHADAP PRESIDEN/ WAKIL PRESIDEN DALAM KUHP BARU PERSPEKTIF ASAS EQUALITY BEFORE THE LAW - YAMIN, BAHRI; AMALIA, FITRIANI; RACHMAN, M.TAUFIK; HARUN, RINA ROHAYU; YULIANI, TIN (Universitas Mahasaraswati K. Mataram, 2024)
The aim to be achieved is to find out and provide scientific information to interested parties and the public, the Government, the DPR RI and the Constitutional Court, that this new Criminal Code is still controversial and problematic, at least in relation to the article regarding insulting the President/Vice President. This research is a type of Normative legal research. Thus, the approach used to answer the legal issues studied in this research is to use a Statutory Approach. The analysis is by means of legal interpretation and analytical descriptive. After the primary legal materials and secondary legal materials have been collected, they are described systematically and methodically in order to obtain a universal picture of the legal issues raised in this research in order to determine the final conclusions. The result is the revival of the article on insulting the President/Vice President, which is contrary to the principle of equality before the law and there is discriminatory legal privilege treatment which is different from the position of the people as the highest holder of sovereignty, which is strengthened by the Constitutional Court Decision Number 013-022/PUU-IV/ 2006. At the same time it is contrary to Article 27 paragraph (1); Article 28; Article 28E paragraphs (2) and (3); Article 28J paragraph (1) and paragraph (2) of the 1945 Constitution of the Republic of Indonesia